Perception about the mobility experience of students in universities: a descriptive study (2023)
Academic mobility is a manner to internationalize the academic curriculum to foster learners' integral development. This article aims to describe the perspective about foreign students' mobility experience in CECAR and about the interns that developed it abroad. This was a quantitative study with a descriptive scope, in which 88 students were surveyed. The results revealed that learners consider that the academic mobility contributed to fostering disciplinary competences and technological and investigative skills. The current research details the value of following up with the students once they return from their academic experience. They also acknowledge this strategy promotes a change in their viewpoints of the world.